Socio-Emotional Literacy And Scholastic Achievement Of Grade Six Pupils - Aurelio Jr, S. Gomez; M. Zainal Arifin (Universitas Pakuan, 2026)
Socio-emotional literacy is a relatively new concept in the educational arena. It has vital importance because it can greatly help improve a child's self-esteem and self-empowerment. However, there seems to be less opportunity in our society to learn the skills of communicating with and relating to others in a healthy positive ways. Thus, one of the new trends in education nowadays is developing the socio-emotional literacy of the learners. This study was conducted in order to assess the socio-emotional literacy and scholastic achievement of the Grade Six Pupils in Magugpo Pilot Central Elementary School in Tagum District. It utilized the Five-point Likert Scale in describing the level of the socio-emotional literacy of the respondents. Pearson r was used to determine the significant relationship between the level of socio-emotional intelligence and scholastic achievement, and the t-test was used in analyzing the significant difference on the socio-emotional literacy of the participants when analyzed according to gender. The findings showed that the emotional literacy of the respondents of the study in terms of self-awareness, self-regulation, self-motivation, social awareness, and social competence were rated with high category which means that they are evident in the participants of the study. Furthermore, the study found out that there was significant difference in the emotional intelligence of the participants when analyzed according to gender. Finally, it was found out that there was significant relationship between the socio-emotional literacy and scholastic achievement of the grade six pupils